Hip strength as an intrinsic risk factor for lateral ankle sprains in youth soccer players: A 3-season prospective study - De Ridder, R.; Witvrouw, E.; Dolphens, M.; Roosen, P.; Van Ginckel, A. (The American Journal of Sports Medicine, 2017)
Background: Numerous epidemiological studies have emphasized the burden of lateral ankle sprains in youth soccer players. However, no prospective study has identified intrinsic physical and modifiable risk factors for these injuries in this particular population. Although injury prevention programs in soccer incorporate proximal hip and core stability exercises, it is striking that the relationship between impaired proximal hip function and ankle sprains has not yet been prospectively investigated in youth soccer players. Hypothesis: This prospective study aimed to examine whether hip muscle strength is a risk factor for sustaining a lateral ankle sprain in youth soccer players. We hypothesized that decreased hip muscle strength would predispose youth soccer players to an increased risk of lateral ankle sprains. Study Design: Case-control study; Level of evidence, 3. Methods: This study included a total of 133 male youth soccer players (age divisions U11-U17) for analysis. At the beginning of the season, anthropometric characteristics were collected and hip muscle strength was assessed using a handheld dynamometer. Injury registration was performed by the team medical staff during 3 consecutive seasons. A principal-component, multivariate Cox regression analysis was performed to identify potential risk factors for sustaining a lateral ankle sprain. Results: Twelve participants (18% of all reported injuries) sustained a lateral ankle sprain (0.36 per 1000 athletic-exposure hours). After adjustment for body size dependencies and other hip muscle forces, an increase in hip muscle extension force was associated with a significant decrease in the hazard of the injury (hazard ratio, 0.3; 95% confidence interval, 0.1-0.9; P = .028). No other study variable could be identified as a risk factor for lateral ankle sprains. Conclusion: Reduced hip extension muscle strength is an independent risk factor for lateral ankle sprains in male youth soccer players. Other hip muscle strength outcomes were not identified as risk factors. Replication in larger samples with more injured cases is warranted to further ascertain the importance of this risk factor.